Acute physiological and perceptual responses to Brazilian jiu-jitsu sparring: the role of maximal oxygen uptake - Øvretveit, K. (International Journal of Performance Analysis in Sport, 2018)
Sparring is a training form in combat sports designed to simulate fighting. This study sought to assess physiological and perceptual responses to Brazilian jiu-jitsu (BJJ) sparring and their relationship with maximal oxygen uptake (VO2max). Twelve male BJJ athletes (age: 30.6 ± 2.7 (SD) years; height: 182.5 ± 5.9 cm; body mass (mb): 81.2 ± 6.7 kg; body fat: 9.9 ± 3.2%) with 4.6 ± 2.2 years of BJJ experience and a training volume of 10.3 ± 4.4 h· week-1 participated in the study. Following a VO2max measurement, heart rate (HR), blood lactate concentration ([La-]b), and rating of perceived exertion were obtained during sparring in a regular training session. Each participant sparred five consecutive 6-min rounds separated by 90-s breaks. Mean sparring HR was 164 ± 9 beats· min-1, equivalent to 85% ± 4% of the maximal HR (HRmax). The sparring was perceived as "hard". Mass-independent VO2max correlated negatively with HR, relative HR (%HRmax), and [La-]b (p <0.05). The inverse relationship between VO2max and physiological markers of exertion suggest that VO2max affects exercise tolerance in BJJ and could also point to a limited efficacy of sparring for developing aerobic endurance due to insufficient exercise intensity in trained athletes.